Did a bi-polar multi-level oceanic oscillation cause the Little Ice Age and other high latitude climate extremes? - Johnson, Robert G. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2015)
Variations of ice-rafted sand and sediment from deep-sea cores beneath the North Atlantic Drift imply 1500yr cycles of the Drift flow and its associated climate warmth in northern North Atlantic regions. The Drift cycle is part of a complex bi-polar oceanic oscillation. Central to the oscillation is the relatively higher sea surface salinity of the high-latitude Greenland Sea that enables the winter sinking of surface water to form North Atlantic Deep Water (NADW). This drives the oscillation, and the NADW is replaced by water from the Drift. The oscillation causes climate extremes in both northern and southern high latitudes and is framed here in a sinusoidal model. The model is consistent with and may explain the early medieval climate optimum, the subsequent Little Ice Age, the recent record maximum area of Antarctic winter sea ice, and the related record low rate of Antarctic Bottom Water (ABW) formation. The negative feedback of lower salinity ABW entering the northern North Atlantic tends to inhibit NADW formation and the northward Drift flow. The positive feedback of warmer and higher salinity NADW mixing into the Southern Ocean around Antarctica tends to reduce sea ice formation and enhance the rate of ABW formation. Because of these feedbacks, the rate of NADW formation oscillates over a range less than a maximum without feedback, the rate of ABW formation oscillates over a range greater than a minimum without feedback, and the phase of NADW oscillation in the model leads the ABW oscillation by 375 years. The model predicts another northern North Atlantic climate optimum about 2500 AD. However, increases in penetration of the polar ocean by flow of Atlantic water in the process of replacing the sinking NADW suggest that an interval of extreme warmth in the northeastern North Atlantic may occur within decades. This penetration could result in the loss of perennial sea ice along the northern coast of Greenland. Much of the inferred increase of northward winter flow of northeastern North Atlantic water into the Greenland Sea in recent decades may be due to stronger NADW formation caused by greater salt contributions to the Drift from the Mediterranean outflow.